Issues in television and social media convergence process - Yoedtadi, Moehammad Gafar; Ronda, Andi Mirza; Wahid, Umaimah (ProTVF, 2024)
Background: Competition between traditional media and social media in reaching the attention of the audience has become a necessity. The presence of social media has changed the pattern of media use in society in seeking entertainment and information. To anticipate these changes, television must converge with social media. Convergence is believed not only to be able to maintain the existence of television but also to increase the number of audiences. Purpose: This study aims to identify and explain the management problem in the process of convergence between social media and television at the IVM (Indosiar Visual Mandiri) television editorial team. Methods: This study uses a qualitative approach and a single case study method. The object of the research is the convergence process between social media and television at the IVM television editorial team; the research subjects are informants consisting of the editor-in-chief, news production manager, reporters, and social media managers. The convergence analysis used in this paper was the journalistic convergence model from Pavlik, which looks at the convergence model in newsrooms, newsgathering, and news content. Results: This study indicates that the convergence of social media and television at the IVM television editorial team does not occur in the newsroom model and only occurs not routinely in the news gathering model and content model. However, in order to converge with social media, television broadcasting encountered problems from the management side (organizational structure, work system, and technology infrastructure). Implications: The convergence of newsrooms between television and social media at IVM can be said to have failed due to the non-integration of social media management with IVM editorial staff. Due to the absence of an integrated social media team within the editorial team, there is a lack of handling of interactivity between social media followers and IVM editors.